PROSES PRODUKSI ALMOND CRISPY UBI JALAR - Sandy Tri Wibowo; Bara Yudhistira; Nur Her Riyadi Parnanto (Jurnal Kewirausahaan dan Bisnis, 2018)
Almond Crispy of sweet potato was inovation of food that included into the cookies product. The processing of Almond Crispy itself carried out with adding of violet sweet potato and yellow sweet potato already through powdering to give new taste towards flavor and content of Almond Crispy product. The process of manufacturing Almond Crispy of sweet potato included the mixing process, the adding of arid ingredient, the casting of dough, the roasting, the colling and the last packaging. The testing of delight sensory carried out to know the level of delight and the potency of consumer accepting. The sample that chosen on sensory testing included the sample of Almond Crispy adding to violet sweet potato, the sample was F3 (50% = 75 gramme) and the sample of Almond Crispy adding to yellow sweet potato, the sample was F1 (30% = 45 gramme). To determine the characteristic of the last product did the testing of antioxidant activity and the sample of violet sweet potato there was (16,45%) and the sample of yellow sweet potato there was (11,83 %), along with the testing of total calorie on violet sweet potato sample that was (4,940 kkal/g) and yellow sweet potato sample that was (5,190 kkal/g). Based on the calculation of economy analysis that did determining concern of HPP,BEP, ROI, POT, NPV and IRR so this effort of Almond Crispy Sweet Potato production can profitable and suitable for operation.